Impact of paddy straw and Bio-decomposer with inorganic fertilizers on soil health in wheat (Triticum aestivum L.) - KUMAR, MANJUL; DAVID, ARUN ALFRED; ARORA, SANJAY (Journal of Soil and Water Conservation, 2026)
The study investigated the effect of inorganic fertilizers, paddy straw (rice residue), and Halo-CRD biodecomposer on the soil health of post-harvest wheat fields in the subtropical region of Prayagraj, Uttar Pradesh during the Rabi season of 2019–20 and 2020-21. Results demonstrated the effectiveness of integrated residue management in improving soil physical, chemical and biological properties. There was a significant build-up of soil organic carbon in T7 (Rice residue treated with microbial decomposer Halo-CRD+ RDF@100%) 0.85 and 0.59% and 0.91 and 0.60% content in soil during both seasons of 2019– 20 and 2020-21. Maximum content of available N (257.26, 261.52 kg ha-1 and 249.43, 251.35 kg ha-1), available P (21.62, 22.14 kg ha-1 and 19.67, 19.85 kg ha-1) and K (219.21, 223.20 kg ha-1 and 181.38, 182.68 kg ha-1) was observed in treatment T7 during both seasons. The bacterial and fungal count ranged from 6.40 to 17.70 ×105 and 3.10 to 8.15×105 cfu g-1 dry soil, respectively. Incorporating microbial decomposers enhanced nutrient-use efficiency and soil health while reducing nutrient losses. The findings advocate integrating rice residue management with microbial decomposer Halo-CRD and balanced fertilization to enhance soil chemical, physical and biological properties, improve soil health, and mitigate residue burning’s environmental impacts.